Changes of PBP5 Gene Expression in Enterococcal Isolates from Renal Transplantation Recipients. (19th June 2013) - Jarzembowski, T.; Daca, A.; Witkowski, J.; Rutkowski, B.; Gołębiewska, J.; Dębska-Ślizień, A.
Abstract : The aim of the study was to evaluate changes in expression of PBP5 gene associated with immunosuppression. A linear locked nucleic acid (LNA) probe was used to measure resistance gene expression by the Flow-FISH method. Expression of the PBP5 gene measured by Flow-FISH was higher in enterococcal strains isolated from renal transplantation (RTx) recipients than in commensal strains. Additionally, in contrast to commensal strains in isolates from RTx patients, PBP5 gene expression was 17.45% higher in biofilms than in planktonic cells. Detailed comparison also showed that cyclosporine seemed to induce higher expression of PBP5 as compared to tacrolimus.